Answer:
![x(x-3)(x+2)](https://tex.z-dn.net/?f=x%28x-3%29%28x%2B2%29)
Step-by-step explanation:
1. Find the GCF (Greatest Common Factor)
![GCF=x](https://tex.z-dn.net/?f=GCF%3Dx)
2. Factor out the GCF and simplify.
![x(x^{2} -x-6)](https://tex.z-dn.net/?f=x%28x%5E%7B2%7D%20-x-6%29)
3. Factor ![x^{2} -x-6.](https://tex.z-dn.net/?f=x%5E%7B2%7D%20-x-6.)
Which two numbers add up to -1 and multiply to -6?
<u>-3 and 2</u>
Rewrite the expression using the numbers above.
![(x-3)(x+2)](https://tex.z-dn.net/?f=%28x-3%29%28x%2B2%29)
4. Done!
![x(x-3)(x+2)](https://tex.z-dn.net/?f=x%28x-3%29%28x%2B2%29)
Answer:
12
Step-by-step explanation:
Answer:
A -2V7
Step-by-step explanation:
you just have to subtract the coefficients
3-5=-2
-2V7
Answer:
<h2>16.26</h2>
Step-by-step explanation:
Pythagorean Theorem | a^2 + b^2 = c^2
1) Plug in a & b
<h2>11^2 + 12^2 = c^2</h2>
2) Rewrite
<h2>c =
![\sqrt{11^2 + 12^2}](https://tex.z-dn.net/?f=%5Csqrt%7B11%5E2%20%2B%2012%5E2%7D)
</h2>
3) Solve
<h2>c = 16.2788206</h2>
4) Round
<h2>16.26</h2>